Organic field-effect transistors integrated with Ti2CTx electrodes. Issue 11 (1st March 2018) - Lai, Shen; Jang, Sung Kyu; Cho, Jeong Ho; Lee, Sungjoo
Abstract : Pentacene organic field-effect transistors integrated with MXene (Ti2 CT x ) electrodes are studied. Superior device performance with high mobility, high on/off ratio, and low contact resistance is achieved. Abstract : Recently, MXenes, which are two-dimensional early transition metal carbides and carbonitrides, have attracted wide attention because of their unique properties. In this study, the electrode applications of Ti2 CT x, a member of the MXene family, in pentacene organic field-effect transistors (OFETs) are assessed. Kelvin probe force microscopy analysis was performed to determine the work function of Ti2 CT x, which is estimated to be around 5.1 eV. Devices with Ti2 CT x electrodes and pentacene channels were fabricated and their electronic performances were evaluated. The contact resistance between Ti2 CT x and pentacene is as low as 3 kΩ cm, superior to those of other reported electrode materials. The temperature-dependent current–voltage transfer characteristics of the devices were used to extract activation energy, estimated to be 0.17 eV. This activation energy value is much lower than those of other electrode materials and demonstrates that Ti2 CT x is a promising electrode for high performance OFET applications.